Theory, Practice, and Applications of Rules on the Web 7th International Symposium, RuleML 2013, Seattle, WA, USA, July 11-13, 2013, Proceedings - Morgenstern, Leora; Stefaneas, Petros; Lévy, Francois; Wyner, Adam; Paschke, Adrian (Programming and Software Engineering,, 2013)
This book constitutes the refereed proceedings of the 7th International RuleML Symposium, RuleML 2013, held in Seattle, WA, USA, in July 2013 - collocated with the 27th AAAI 2013. The 22 full papers,12 technical papers in main track, 3 technical papers in human language technology track, and 4 tutorials presented together with 3 invited talks were carefully reviewed and selected from numerous submissions. The accepted papers address topics such as rule-based programming and rule-based systems including production rules systems, logic programming rule engines, and business rules engines/business rules management systems; Semantic Web rule languages and rule standards; rule-based event processing languages (EPLs) and technologies; and research on inference rules, transformation rules, decision rules, production rules, and ECA rules.